Unusual feeding behaviour of the House Sparrow "Passer domesticus" in Slowinski National Park, Poland - Jędro, Grzegorz; Jędro, Magdalena (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In this note we report two infrequent predatory behaviour patterns of the House Sparrow, both diurnal and nocturnal.
Keywords: wróblowe; ornitologia